Changing Share Price After Announcement Of The Merger And Acquisitions By Acquiring Firms Is Significant Or Insignificant - Khan, Arif Hasan; Belal Uddin (Profesional Muda Cendekia Publishing, 2024)
This Paper scrutinizes a model of merger and acquisition declaration of different companies in United Kingdom (Home Takeover) region and also other countries (Cross-Border Takeover) during the time period of 01 January 2019 to 30 June 2022 and finally displays the consequence of 50 Home takeover companies (UK companies acquired UK companies) and 50 cross- border companies (UK companies take over foreign companies) to recognize the post effect of merger andacquisition declaration on the stock prices of the target and acquired firms. Event Study Methodology has been used for this study, like, Average Abnormal Returns (AAR) and Cumulative Average Abnormal Returns (CAAR) are used to analyze the different event windows about the stock prices of the target and acquired firms. A paired sample investigation has also been directed by associating the Pre- and Post- announcement returns on stock prices for the event window of ± 5 days of the target and acquired firms. In the event windows, the stock price of the target firm's all is not positive CAAR but pointedly dissimilar from zero. In the home takeover figures, all the AAR and CAAR are not significant and some negative returns after the post-declaration prove about the primary investor's overreaction and efficient market hypothesis (EMH). There is no presence of positive implication in the cross-border pre-event return but only a positive implication returns in the home takeover pre-event return that is also significant at the 10% level.